The Mediating Effect of Marketing Capabilities on the relationship between Entrepreneurial Orientation and SMEs' performance: An Empirical Study in Oman - Alshanfari, Khalid Salim; Jantan, Mohd Dan (Technium Social Sciences Journal, 2022)
Literature has indicated ambiguity remains as to the firms' capabilities that enhance the relationship between entrepreneurial orientation (EO) and firms' performance, especially in developing nations' SMEs. Thus, this study investigates the marketing capabilities (planning (MPC) and implementation (MIC)) as two-capabilities that mediate the EO-performance relationship in Oman SMEs. A survey of SMEs' managers/owners was undertaken in Oman and a total of 353 useable questionnaires were received for empirical research for the suggested model, utilizing a structural-equation model (Smart-PLS). The results demonstrated EO, MPC, and MIC favorably improve SMEs' performance, and EO affects positively and significantly MPC and MIC. MPC and MIC partially mediate EO-SMEs' performance relationship. The findings contribute to the literature by illustrating the relevance of EO as (a strategic-resource), with MPC and MIC (as dynamic-capabilities) in improving SMEs' performance. By understanding the model's components, SMEs' managers/owners can maximise internal resources and capabilities to boost performance.